Rhetorical construction of corruption - Ángel, Adriana (2016)
By embracing a rhetorical approach, this manuscript analyzes how highranking government officials communicate the idea of corruption in relation to the recent scandals of corruption denounced in this country. Rhetorical cluster analysis was used to explore the Guatemalan rhetorical construction of corruption. This analysis led to the identification of three main terministic screens of corruption such as Fraud, Democracy, and Interventionism and showed the use of two rhetorical resources: Accreditation and reference to evidence. It concludes that these clusters and rhetorical devices lead to the normalization of corruption and to the establishment of weak programs of action against this phenomenon.